2017
DOI: 10.1007/s40544-017-0182-6
|View full text |Cite
|
Sign up to set email alerts
|

Study on frictional behavior of carbon nanotube thin films with respect to surface condition

Abstract: In this work, tribological characteristics of thin films composed of entangled carbon nanotubes (CNTs) were investigated. The surface roughness of CNT thin films fabricated via a dip-coating process was controlled by squeezing during the process with an applied normal force ranging from 0 to 5 kgf. Raman spectra and scanning electron microscopy (SEM) images of the thin films were obtained to estimate the influence of the squeezing process on the crystallinity of the CNTs. The analysis revealed that squeezing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, according to the effect of the reinforcement ratio in both Figure 6 and Figure 9 , it can be interpreted that there is a strong relationship between surface roughness and COF values. Such an interaction has been reported in different studies in the literature [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 58%
“…In addition, according to the effect of the reinforcement ratio in both Figure 6 and Figure 9 , it can be interpreted that there is a strong relationship between surface roughness and COF values. Such an interaction has been reported in different studies in the literature [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 58%
“…The temperature values, which are instantaneously reached during wear and described as the flash temperature, are considerably higher than the average temperature values of this contact zone. This causes the bronze to exhibit a significant amount of adhesive behavior in the later stages of wear and finally to plaster the bronze to the surface [24,61,67]. to 40 wt% is beneficial for wear rate characteristics.…”
Section: Interpretation Of Experimental Results and Parameter Optimization For Temperature Changementioning
confidence: 99%
“…Rougher surface quality, which increases the friction coefficient, also elevates the temperature of the contact zone. Different studies [ 67 , 68 ] have reported such an interaction between surface quality and coefficient of friction.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, lubricants which mainly include solid lubricants and liquid lubricants are widely used for lubrication. There are many advanced solid lubricants such as molybdenum disulfide (MoS 2 ) film [7], diamond-like coating [8], entangled carbon nanotube (CNT) film [9], and polymer material [10,11]. However, their tribological properties are directly influenced by the friction environment, and they are prone to being a wear-out failure after serving for a long time.…”
Section: Frictionmentioning
confidence: 99%